Mitigating cold start problem in serverless computing with function fusion - Lee, Seungjun; Yoon, Daegun; Yeo, Sangho; Oh, Sangyoon (Sensors, 2021)
As Artificial Intelligence (AI) is becoming ubiquitous in many applications, serverless computing is also emerging as a building block for developing cloud-based AI services. Serverless computing has received much interest because of its simplicity, scalability, and resource efficiency. However, due to the trade-off with resource efficiency, serverless computing suffers from the cold start problem, that is, a latency between a request arrival and function execution. The cold start problem significantly influences the overall response time of workflow that consists of functions because the cold start may occur in every function within the workflow. Function fusion can be one of the solutions to mitigate the cold start latency of a workflow. If two functions are fused into a single function, the cold start of the second function is removed; however, if parallel functions are fused, the workflow response time can be increased because the parallel functions run sequentially even if the cold start latency is reduced. This study presents an approach to mitigate the cold start latency of a workflow using function fusion while considering a parallel run. First, we identify three latencies that affect response time, present a workflow response time model considering the latency, and efficiently find a fusion solution that can optimize the response time on the cold start. Our method shows a response time of 28–86% of the response time of the original workflow in five workflows.
Keywords: Building blockes; Cloud-based; Cold start problems; Cold-start; Function fusion; Parallel functions; Resource efficiencies; Serverless computing; Serverless workflow; Work-flows; Artificial Intelligence; Software; Workflow; Function fusion; Serverless computing; Serverless workflow